Shelf life assessment of fishery product. By: Suryanti and Theresia Dwi Suryaningrum - suryanti, suryanti (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2010)
The processing of fishery product is a preservation way to maintain its shelf life. The shelf life offishery product is very crucial, since it is an important source of animal protein which is easilydegraded by microbial activity and enzymatic reaction. Furthermore, fish also contains highunsaturated fatty acid which is easy to oxidize and produce rancid odor. The shelf life prediction offishery product is usually studied using conventional(ESS) and accelerated method (ASLT) Arheniusmodel. The conventional method predicts the shelf life of food product at the normal condition andobserve the parameter of quality degradation until the expired quality is reached. ASLT methodArhenius model predicts the shelf life of food product with accelerate the quality degradationbecause of effect temperature. The conventional method can be applied for wet and semi-wetproducts, such as fish fillet and fish burger, where as Arhenius model can be applied for wet, semiwet and dry products, such as frozen shrimp and dendeng fish.